Impaired Motor Function in the Affected Arm Predicts Impaired Postural Balance After Stroke: A Cross Sectional Study - Rafsten, Lena; Meirelles, Christiane; Danielsson, Anna; Sunnerhagen, Katharina S. (Frontiers in Neurology, 2019)
Background: Impaired postural balance is a common symptom after stroke and a common cause of falling. Arm and hand movements are used in most common daily tasks. Impairment in an upper extremity is a common symptom that affects 50-80% in the acute phase after stroke, and 40-50% in the sub-acute phase. Several studies show that the leg function impacts postural balance, but few studies have shown the importance of arms on postural balance. The goal of this cross sectional study is therefore to explore if there is any association between arm function and postural balance after stroke. Method: In total 121 adults (mean age: 70 ± 12.3 years, 72 men) from an accessibility population were included. Eighty nine came from the stroke unit and 32 came from the Rehabilitation Clinic. The dependent outcomes were Bergs Balance scale (BBS) and Time Up and Go (TUG) both dichotomized to impaired postural balance and not impaired postural balance. As independent variables, the Fugl-Meyer Assessment-Upper Extremity (FMA-UE) scale was used. The FMA-UE was presented with the total score. Results: Time since stroke ranged from 1-13 years. The motor function in the arm affected after stroke onset correlated with postural balance both measured with the BBS (0.321, p<0.001) and the TUG (-0.315, p=0.001). Having impaired motor function in the arm were significant associated with impaired postural balance assessed with the BBS with OR= 0.879. Regression analysis with the TUG showed the same result, OR= 0.868 for FM-UE. Conclusion: The muscular function of the affected arm significant associate with impaired postural balance post stroke assessed with BBS or TUG. It can be of clinical importance to be aware of the fact that not only lower extremity impairment, but also arm function can have an impact on postural balance in late stage after stroke. Trial registration: VGFOUGSB-669501